Mobilizing Law in Latin America: An Evaluation of Black's Theory in Brazil. Issue 2 (25th April 2012) - Graham, Kristin Tennyson; Borg, Marian J.; Miller, Bryan Lee
<x xml:space="preserve">Abstract</x> This research addresses two separate but related questions. First, to what extent are sociological theories proposed to explain legal behavior in Western societies applicable to non‐Western contexts? And second, to what degree is Black's theory of law generalizable, as he contends, "across time and space?" Our research merges these questions by exploring the applicability of Black's theory in a Latin American context. Data collected from a nationally representative survey in Brazil suggest support for Black's propositions regarding the impact of vertical, horizontal, cultural, and normative status on the likelihood of mobilizing the law, as well as the feasibility of using his framework for understanding legal behavior in non‐Western settings. Our discussion considers implications and directions for future analyses in both the Brazilian and cross‐cultural contexts.